The effects of a Virtual Fracture Care review protocol on secondary healthcare utilization in trauma patients requiring semi-acute surgery: a retrospective cohort study - G. J. A. Willinge; J. F. Spierings; T. H. Geerdink; B. A. Twigt; J. C. Goslings; R. N. van Veen (Frontiers Media S.A., 2024)
PurposeThe demand for trauma care in the Netherlands is increasing due to a rising incidence of injuries. To provide adequate trauma care amidst this increasing pressure, a Virtual Fracture Care (VFC) review protocol was introduced for treatment of musculoskeletal injuries to the extremities (MIE). This study aimed to assess the influence of the Dutch VFC review protocol on secondary healthcare utilization (i.e., follow-up appointments and imaging) in adult trauma patients (aged ≥18 years) who underwent semi-acute surgery (2-14 days after initial presentation) for MIE, compared to traditional workflows. We hypothesized utilization of VFC review would lead to reduced secondary healthcare utilization.MethodsThis retrospective cohort study assessed the influence of VFC review on secondary healthcare utilization in adult trauma patients (aged ≥18 years) who underwent semi-acute surgery for a MIE. Patients treated before VFC review and the COVID-19 pandemic, from 1st of July 2018 to 31st of December 2019, formed a pre-VFC group. Patients treated after VFC review implementation from January 1st 2021 to June 30th 2022, partially during and after the COVID-19 pandemic (including distancing measures), formed a VFC group. Outcomes were follow-up appointments, radiographic imaging, time to surgery, emergency department reattendances, and complications. The study was approved by the local ethical research committee approved this study (WO 23.073).ResultsIn total, 2,682 patients were included, consisting of 1,277 pre-VFC patients, and 1,405 VFC patients. Following VFC review, the total number of follow-up appointments reduced by 21% and a shift from face-to-face towards telephone consultations occurred with 19% of follow-up appointments performed by telephone in the VFC group vs. 4% in the pre-VFC group. Additionally, VFC review resulted in a 7% reduction of radiographs, improved time scheduling of surgery, and a 56% reduction of emergency department reattendances. Registered complication rates remained similar.ConclusionThe utilization of VFC review for management of adult patients with a MIE requiring semi-acute surgery improves efficiency compared to traditional workflows. It results in a 21% follow-up appointment reduction, a shift from face-to-face to remote delivery of care, fewer radiographs, improved time scheduling of surgery, and reduces emergency department reattendances by 56%.